In-silico study of E169G and F242K double mutations in leucine-rich repeats (LRR) polygalacturonase inhibiting protein (PGIP) of Gossypium barbadense and associated defense mechanism against plant pathogens - Sneha Murmu; Mayank Rashmi; Dipak T. Nagrale; Tejasman Kour; Mahender Kumar Singh; Anurag Chaurasia; Santosh Kumar Behera; Raja Shankar; Rajiv Ranjan; Girish Kumar Jha; Shailesh P. Gawande; Neelakanth S. Hiremani; et al. (Journal of Cotton Research)
Abstract Background Polygalacturonase inhibiting proteins (PGIPs) play a pivotal role in plant defense against plant pathogens by inhibiting polygalacturonase (PG), an enzyme produced by pathogens to degrade plant cell wall pectin. PGIPs, also known as leucine-rich repeat pathogenesis-related (PR) proteins, activate the host’s defense response upon interaction with PG, thereby reinforcing the host defense against plant pathogens attacks. In Egyptian or extra-long staple cotton (Gossypium barbadense), the interaction between PGIP and PG is one of the crucial steps in the defense mechanism against major pathogens such as Xanthomonas citri pv. malvacearum and Alternaria macrospora, which are responsible for bacterial leaf blight and leaf spot diseases, respectively. Results To unravel the molecular mechanisms underlying these PR proteins, we conducted a comprehensive study involving molecular modeling, protein-protein docking, site-specific double mutation (E169G and F242K), and molecular dynamics simulations. Both wild-type and mutated cotton PGIPs were examined in the interaction with the PG enzyme of a bacterial and fungal pathogen. Our findings revealed that changes in conformations of double-mutated residues in the active site of PGIP lead to the inhibition of PG binding. The molecular dynamics simulation studies provide insights into the dynamic behaviour and stability of the PGIP-PG complexes, shedding light on the intricate details of the inhibitory and exhibitory mechanism against the major fungal and bacterial pathogens of G. barbadense, respectively. Conclusions The findings of this study not only enhance our understanding of the molecular interactions between PGs of Xanthomonas citri pv. malvacearum and Alternaria macrospora and PGIP of G. barbadense but also present a potential strategy for developing the disease-resistant cotton varieties. By variations in the binding affinities of PGs through specific mutations in PGIP, this research offers promising avenues for the development of enhanced resistance to cotton plants against bacterial leaf blight and leaf spot diseases.